Highly oxidized low‐density lipoprotein mediates activation of monocytes but does not confer interleukin‐1β secretion nor interleukin‐15 transpresentation function. Issue 2 (21st November 2019) - Sieg, Scott F.; Bazdar, Douglas A.; Zidar, David; Freeman, Michael; Lederman, Michael M.; Funderburg, Nicholas T.
Summary: Oxidized low‐density lipoprotein (LDL) contributes to cardiovascular disease in part by mediating activation and maturation of monocytes and macrophages. Furthermore, co‐localization studies using histochemical approaches have implicated a potential role for oxidized LDL as a mediator of interleukin‐15 (IL‐15) expression in myeloid cells of atherosclerotic plaque. The latter activity could be an important pro‐inflammatory mechanism that mediates myeloid cell/T‐cell crosstalk. Here, we examined the responses of primary human monocytes to highly oxidized LDL molecules. Oxidized LDL readily induced secretion of chemokines MCP‐1 (CCL2) and GRO‐ α (CXCL1) but unlike lipopolysaccharide (LPS), has limited capacity to induce a variety of other cytokines including tumor necrosis factor‐ α, IL‐6, IL‐1 β and interferon‐ γ ‐induced protein‐10 and also displayed a poor capacity to induce p‐Akt or P‐S6 signaling. Failure of oxidized LDL to induce IL‐1 β secretion was associated with limited induction of caspase‐1 activation. Furthermore, despite finding evidence that oxidized LDL could enhance the expression of IL‐15 and IL‐15 receptor expression in monocytes, we found no evidence that it could confer IL‐15 transpresentation capability to these cells. This observation contrasted with induction of IL‐15 transpresentation in lipopolysaccharide‐stimulated monocytes. Overall, our data suggest that highly oxidized LDL is a selective inducer of monocyte activation. Sterile inflammatory mediators, particularly those implicated in Toll‐like receptor 4 signaling, may play a role in vascular pathology but the activities of these agents are not uniform. Abstract : Oxidized low‐density lipoprotein (LDL) plays an important role in generation of foam cells during atherosclerotic disease, but its role in induction of inflammatory monocytes/macrophages is less clear. We find that highly oxidized LDL molecules only modestly activate primary monocytes, failing to induce interleukin‐1 β (IL‐1 β ) secretion and IL15/IL15 receptor transpresentation activity in these cells. Our results suggest that other mediators may play a more substantial role in inflammatory monocyte activation in atherosclerosis.